Biochemical changes involved in self-incompatibility in two cultivars of olive (Olea europaea L.) during flower development. Issue 2 (3rd March 2016) - Aslmoshtaghi, E.; Shahsavar, A. R.
ABSTRACT: Biochemical analyses were carried out to characterise the basis of self-incompatibility in the olive ( Olea europaea L.) cultivars 'Amygdalolia' and 'Konservalia'. Multiple interactions between cells of different types, origin, and function occur in the pistil. Endogenous factors play important roles in ovary and fruit development before (Stage 1) and during pollination (Stage 2), and after fertilisation (Stage 3). Changes in carbohydrate, protein, H2 O2, and calcium ion concentrations, and in peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase activities in pistil tissue before and during pollination, and after fertilisation were investigated. In both cultivars, H2 O2 concentrations were significantly higher in pistil tissue before pollination, after which they started to decrease in Stage 2 and continued non-significantly in Stage 3. Peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase activities were lower at Stage 1 and Stage 2, whereas these enzyme activities increased at Stage 3 in both cultivars. The lowest concentration of calcium ions was observed at Stage 1, whereas at Stage 2, calcium ion concentrations increased and reached their highest level, then decreased at Stage 3. Calcium ion concentrations in 'Konservalia' were higher than in 'Amygdalolia'. In 'Konservalia', the highest protein concentration was observed at Stage 2. No significant differences were found in carbohydrate concentrations between the two cultivars. The biological significance of the presence of these products may differ between Stage 1, when they have a defence function, Stage 2 when there are interactions between pollen and pistil, and Stage 3 after fertilisation. This study provides support for the hypothesis that there is a correlation between self-incompatibility, stress-related enzyme activities, and calcium ion concentrations in the pistils of olive.